Interaction of inherited structures and contractional deformation in the South Dezful Embayment: Insights from the Gachsaran oilfield, SW Iran - Shamszadeh, Aref; Sarkarinejad, Khalil; Ferrer, Oriol; Mukherjee, Soumyajit; Seraj, Mohammad (Marine and petroleum geology, 2022)
Identifying the timing, geometry, mechanism and multiphase reactivation of the inherited structures on the structural style of the fold-and-thrust belt is important for hydrocarbon exploration and production. In this work, we present a multidisciplinary approach including field data, seismic profiles, well data analyses, isopach maps, 2D balanced cross-sections construction, and 2D sequential restoration. Such an approach is applied to decipher the multiphase deformation of the NNE-SSW trending deep-seated Kharg-Mish Fault (KMF) that controlled the tectono-sedimentary evolution and structural style of the Gachsaran Anticline (South Dezful Embayment - SDE). Kinematic analysis of the KMF reveals two different mechanisms from normal to reverse faulting (positive inversion) since the Cenomanian. From the Late Cretaceous-Late Miocene, the sedimentary cover thickness ∼2500 m decreases along-strike of the Gachsaran Anticline towards the east, over the KMF, due to regional erosion and pinch-out. The eastern sector of the Gachsaran Anticline shows an angular and smaller wavelength fold in the levels of Asmari and Sarvak formations due to the efficient local middle décollements of the Kazhdumi and Pabdeh formations. Different amounts of shortening, 19.4% for the western and 16.7% for the eastern sector, and fore-thrust propagation developed a tear fault that accommodated differential deformation. Long-term structural evolution and strain localization in the eastern sector of the Gachsaran Anticline over the KMF produced dense fracturing. Our study suggests that mechanism and timing of deformation along the pre-existing basement structures are important in structural evolution of the sedimentary cover, oil migration and accumulation in such a hydrocarbon province. •2D sequential restoration evaluates the tectono-sedimentary evolution of the deep-seated Kharg-Mish Fault (KMF).•Reactivations of KMF Since the Late Cretaceous strongly controlled the thickness of sediments along the Gachsaran Anticline.•Positive inversion tectonics of the KMF is related to the Zagros orogen's oblique contraction.